Thermodynamic Analysis of Radiating Nanofluids Mixed Convection within Concentric Pipes Filled with a Porous Medium - MAKINDE, Oluwole Daniel; MABOOD, Fazle; KHAN, Waqar Ahmed; MAKINDE, Anuoluwa Esther (Engineering Transactions, 2023)
In this study, the entropy generation resulting from heat and mass transfer of water-based nanofluid through an annulus within two concentric vertical pipes filled with a porous medium is investigated. This study considers the effects of thermal radiation, viscous dissipation, thermal buoyancy, and axial pressure gradient in addition to heat and mass transfer. Brownian motion and thermophoresis have been introduced through the Buongiorno model. The similarity solution was used to solve nonlinear ordinary differential equations. The Runge-Kutta-Fehlberg method is used to solve these equations with the related boundary conditions. The effects of pertinent parameters such as pressure gradient, thermal radiation, viscosity parameter, thermophoretic parameter, Brownian motion parameter, and Eckert number are investigated numerically. This study found that the Bejan number increases as the viscosity parameter increases and decreases as the other active parameters increase. As the radiation parameter, thermophoretic parameter, Brownian parameter, and Eckert number increase, the Nusselt number decreases. The total entropy generation rate is found to increase with the fluid viscosity rate, Grashof number, thermal Biot number, and variable pressure gradient. However, the Bejan number is found to decrease with these parameters, as well as the Prandtl number.